Abordagem multidisciplinar da paisagem agropecuária: qualidade de pastagem sob as lentes de geotecnologias e a visão do produtor - Ribeiro, Joyce Amaral (2023)
The agroecosystem is a complex structure that requires a holistic analysis at the landscape level and should not be considered merely as an isolated agricultural production site. It is essential to examine the relationships among people, crops, animals, soil, and water to promote the integration of new technologies. In this regard, this research plays an important role in using remote sensing to study a diverse agroecosystem with the aim of analyzing the behavior of different tree density levels on pasture areas and investigating whether this influence is perceived by family farmers in the Amazon Portal. By using CBERS-4A satellite images in the Jacaminho Settlement Project, it was possible to map tree coverage and delimit sample areas with "High, Medium, and Low" tree densities. The Normalized Difference Vegetation Index (NDVI) was calculated for images from four different dates. It was observed that areas with higher tree densities (20-30%) exhibited the best average NDVI during the dry season. The interviewed farmers highlighted the benefits of trees in their pastures and pointed out the lack of planning in implementing tree areas due to the absence of supportive public policies. Remote sensing proved to be effective in measuring pasture quality based on tree arrangements.